Unconventional Monetary Policy Normalization in High-Income Countries : Implications for Emerging Market Capital Flows and Crisis Risks - Burns, Andrew; Kida, Mizuho; Lim, Jamus Jerome; Mohapatra, Sanket; Stocker, Marc (World Bank, Washington, DC, 2014)
As the recovery in high-income countries firms amid a gradual withdrawal of extraordinary monetary stimulus, developing countries can expect stronger demand for their exports as global trade regains momentum, but also rising interest rates and potentially weaker capital inflows. This paper assesses the implications of a normalization of policy and activity in high-income countries for financial flows and crisis risks in developing countries. In the most likely scenario, a relatively orderly process of normalization would imply a slowdown in capital inflows amounting to 0.6 percent of developing-country GDP between 2013 and 2016, driven in particular by weaker portfolio investments. However, the risk of more abrupt adjustments remains significant, especially if increased market volatility accompanies the unwinding of unprecedented central bank interventions. According to simulations, abrupt changes in market expectations, resulting in global bond yields increasing by 100 to 200 basis points within a couple of quarters, could lead to a sharp reduction in capital inflows to developing countries by between 50 and 80 percent for several months. Evidence from past banking crises suggests that countries having seen a substantial expansion of domestic credit over the past five years, deteriorating current account balances, high levels of foreign and short-term debt, and over-valued exchange rates could be more at risk in current circumstances. Countries with adequate policy buffers and investor confidence may be able to rely on market mechanisms and countercyclical macroeconomic and prudential policies to deal with a retrenchment of foreign capital. In other cases, where the scope for maneuver is more limited, countries may be forced to tighten fiscal and monetary policy to reduce financing needs and attract additional inflows.